Emergency nursing triage and rapid management of suspected acute coronary syndrome: A systematic review - Kafi Pangki Suwito; Abil Rudi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Coronary heart disease (CHD) is a major cause of morbidity and mortality worldwide. Timely triage and rapid management in the emergency department (ED) are essential to improve clinical outcomes and reduce the risk of serious complications. However, uncertainty remains regarding the effectiveness and implementation of various triage strategies across different healthcare settings. Purpose: To systematically analyze the literature on triage strategies and rapid management of patients with coronary heart disease (CHD) in the emergency department (ED). Method: A systematic literature review (SLR) was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature published between 2022 and 2025 was retrieved from Scopus, ScienceDirect, Google Scholar, and DOAJ to synthesize the available scientific evidence. Results: The review showed that triage and emergency management strategies for CHD have undergone substantial innovation, particularly through the development of advanced diagnostic tools such as high-sensitivity troponin biomarkers, clinical scoring systems including the Marburg Heart Score and EDICAS, early imaging modalities such as computed tomography coronary angiography and point-of-care ultrasound, and the integration of artificial intelligence and telecardiology. These approaches improved diagnostic accuracy and workflow efficiency. Their implementation substantially shortened resuscitation and reperfusion times, increased successful rescue rates, improved left ventricular ejection fraction, and reduced door-to-balloon time, thereby contributing to lower mortality and morbidity. Nevertheless, implementation remains constrained by disparities in care associated with sex, race, socioeconomic status, limited trained personnel, healthcare facilities, and the absence of internationally standardized protocols. Conclusion: The findings suggest that recent advances in CHD triage and rapid management provide substantial clinical benefits by improving diagnostic accuracy, treatment efficiency, and patient outcomes. However, continued efforts are needed to address implementation challenges and healthcare disparities to achieve more equitable and effective emergency care.